Short-term exposure to fine particulate matter and genome-wide DNA methylation in chronic obstructive pulmonary disease: A panel study conducted in Beijing, China - Duan, Ruirui; Niu, Hongtao; Dong, Fen; Yu, Tao; Li, Xuexin; Wu, Hanna; Zhang, Yushi; Yang, Ting (Frontiers in Public Health, 2023)
Background: Fine particulate matter (PM2.5) is a crucial risk factor for chronic obstructive pulmonary disease (COPD). However, the mechanisms whereby PM2.5 contribute to COPD risk have not been fully elucidated. Accumulating evidence suggests that epigenetics, including DNA methylation, play an important role in this process; however, the association between PM2.5 exposure and genome-wide DNA methylation in patients with COPD has not been studied. Objective: To evaluate the effect of personal exposure to PM2.5 on genome-wide DNA methylation changes in the peripheral blood of patients with COPD (n = 24). Methods: A panel study was conducted in Beijing, China. We repeatedly measured and collected personal PM2.5 data for 72 h. Genome-wide DNA-methylation of peripheral blood was analyzed using the Illumina Infinium Human Methylation BeadChip (850k). A linear-mixed effect model was used to identify the cytosine-phosphate-guanine (CpGs) associated with PM2.5. Finally, we performed a functional enrichment analysis of the CpG sites that were significantly associated with PM2.5. Results: When the false discovery rate was <0.05, 19 unique CpG sites were significantly correlated with PM2.5, which were annotated as specific genes. Functional enrichment analysis of these genes showed that they were related to the response to toxic substances, regulation of tumor necrosis factor superfamily cytokine production, regulation of photosensitivity 3-kinase signaling, and other pathways. Conclusion: This study provided evidence for a significant relationship between personal PM2.5 exposure and DNA methylation in patients with COPD. Our research also revealed a new biological pathway explaining the adverse effects of PM2.5 exposure on COPD risk.